Pengaruh Kompetensi Guru Pendidikan Agama Islam dan Model Pembelajaran terhadap Pembentukan Karakter Siswa di SMA Islam Parlaungan Waru Sidoarjo - Putra, Muhammad Alamsyah; Masfufah, Masfufah; Majid, Amir Bandar Abdul (ISLAMIKA, 2025)
Students must have character in accordance with norms and ethical values, to shape the character students need to apply learning models that can support student character formation. Teachers of Islamic education are required to master the competencies aimed at providing quality learning so that students can be accepted with maximum. The competencies that teachers of Islamic education and the model of discharge used are important factors to be able to realize students with character. The purpose of this research is to find out the influence of PAI teacher competence and learning models on student character formation, the type of research used in this study is quantitative research. The total number of samples used for this investigation is 64 respondents, the method of sampling this study is Purposive Sampling. The analysis test used for this study is a double linear regression technique with the help of a statistical program tool such as SPSS 26. The results of the test and interpretation in this study can be concluded, Teacher's Competence in Islamic Education (X₁) have a significant and positive influence on Student Character Formation (Y) with a score of 0.316 with t-statistics 2.959 and p-values 0.004 < 0.050. The Learning Model (X₂) has a significant, positive impact on Students' Characters Formation with a value of 0.672 with a t-static of 5.422 and a p- values of 0,000< 0.050.